Homology-mediated transformation of frog-killing fungus Batrachochytrium dendrobatidis illuminates chytrid development and pathogenesis - Stephanie M. Brody; Erik Kalinka; Sarah M. Prostak; Tamilie Carvalho; Jarrett Man; Timothy Y. James; Lillian K. Fritz-Laylin (Proceedings of the National Academy of Sciences, 2025)
The chytrid fungus Batrachochytrium dendrobatidis ( Bd ) infects amphibians and causes chytridiomycosis, a disease linked to global amphibian decline. Despite its ecological importance, Bd has lacked robust tools for genetic manipulation, limiting molecular insights into its development and pathogenicity. Here, we establish homologous recombination as a system for stable transformation of Bd , enabling targeted chromosomal integration of exogenous DNA, endogenous protein tagging, and targeted gene deletion. We use this system to visualize Bd infection in live amphibians to enhance understanding of host invasion and pathogenesis. We also use this system to test a previous hypothesis regarding the role of chitin synthases in Bd development by tagging the endogenous chitin synthase Myo17D and observing its rapid relocalization to the plasma membrane during de novo cell wall assembly. Finally, we use our homologous recombination approach for targeted gene deletion by knocking out the URA3 locus, and confirm the resulting genotype and phenotype via sequencing and drug resistance assays. This genetic transformation system offers a foundational tool for molecular studies of Bd , advancing our capacity to dissect molecular mechanisms of chytrid pathogenesis.